FRAUD IN THE BUMN ENVIRONMENT: ISO 37001:2016 AS AN ANTI-BRIBERY MANAGEMENT SYSTEM (SMAP) - Azkia Nur Aulia; Handoyo Prasetyo (RADJA PUBLIKA, 2025)
Fraud or fraud in State-Owned Enterprises (BUMN) is still a serious problem that threatens the integrity and accountability of state-owned corporations. This study aims to analyze the contribution and strategy of strengthening the application of ISO 37001:2016 as an Anti-Bribery Management System (SMAP) in preventing fraud in the BUMN environment. This research uses a normative juridical method with a statutory approach, conceptual approach, and comparative approach. The results showed that ISO 37001:2016 plays an important role in forming an internal control system. A comparative study of PT Perusahaan Listrik Negara (Persero) and PT Semen Indonesia (Persero) Tbk shows the successful implementation of ISO 37001:2016, while PT Dok and Perkapalan Surabaya (Persero) has not implemented the standard. This study recommends that all SOEs adopt ISO 37001:2016 substantively, strengthening institutional capacity, integrating governance systems and managerial commitment consistently to build a fraud-free business.